Correction: Glomangiomyoma of the Knee: A Rare Juxtasynovial Presentation. Issue 1 (1st June 2020) - Hustings, Nico; Vanhoenacker, Filip; De Backer, Adelard
This article details a correction to the article: Hustings N, Vanhoenacker F, De Backer A. Glomangiomyoma of the Knee: A Rare Juxtasynovial Presentation: Juxtasynovial glomangiomyoma in the joint capsule is a rare location for glomus tumors that should be considered in the differential diagnosis of hypervascular synovial-based tumors. Journal of the Belgian Society of Radiology. 2020;104(1):12. DOI:http://doi.org/10.5334/jbsr.2051 .